Monitoring and evaluating the performance of tourist facility - Pavlović, Dejana (Hotel and Tourism Management, 2013)
The aim of this study is to identify and explore research methods for work performance evaluation. Also, it will define work process activities, and look into employees’ training. Work efficiency management includes identification, assessment measures, process improvement and, sometimes, developing a system for rewarding employees. In order to manage work performance, it is necessary to conduct evaluations of achievements as this is the way for receiving quality information on the parameters essential to the fulfillment of a collective goal. Work performance evaluation is a process of continuous monitoring, evaluating, directing and adjusting the results to achieve the organization goals. The implementation of these processes is of great importance for business in conditions of high uncertainty and competitive environment.